Analysis of the diatom assemblages from Holocene sediments of core IT17RS-GC3 from Edisto Inlet, Ross Sea, Antarctica. - GORO, ALESSANDRO (Pisa University, 2023)
This thesis deals with the study of fossil diatom assemblages from the core IT17RS-GC3 collected in the Edisto inlet (Ross Sea, Antarctica). The objective is to reconstruct the climatic variation of the Holocene, analysing the samples taken from the core, that were prepared for the diatom counting. The diatoms have been widely used as a paleoenvironmental index of past environments, sea-ice and paleo productivity. Sixty samples have been studied following the standard methods of Rathburn et al., (1997), the species were recognized following the methods of Round et al., (1990), Hasle and Syvertsen (1997), Scott and Thomas (2005), Crosta and Koç (2007), Cefarelli et al., (2010). A statistical analysis was done to determine to which ecological parameter the abundance of the species depends on, to increase the interpretability of the data and reconstruct the paleoenvironments. Statistical analysis (Principal component analysis, PCA) highlighted that the most important species regulating the similarity of the different samples (intervals) are Fragilariopsis curta, F. cylindrus, Corethron pennatum and Chaetoceros dichaeta. The identification of these species allowed me to recognise the most important ecological parameters influencing the paleoenvironmental evolution of the Inlet (basically the presence/absence of sea-ice). Therefore, the trends of these species along the core have been investigated first. Subsequently, the ecological requirements and trends of the other common species (>3% of total diatom assemblage) have been investigated to complete the paleoenvironmental frame of the Inlet. Two groups of diatoms were recognized based on their ecology: the open ocean group and the sea-ice group. These species indicate a change in the annual formation of light and dark laminae level with an interruption in the section I of the core IT17RS-GC3 from 87 cm of depth upward, that it is correlated to an annual to multiyear closure of the Edisto inlet with sea-ice, in this circumstance only dark laminae are formed. The ...